DESKRIPSI PEMAHAMAN NILAI GOTONG ROYONG PADA PESERTA DIDIK KELAS 5 DI SEKOLAH DASAR - Iradah, Wasfia; Adiasti, Nindya; Wahid, Sucahyo Mas'an Al (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2026)
Low student participation and lack of student initiative in learning are factors that hinder learning success. This study aims to describe the understanding of the value of mutual cooperation among 5th grade students in elementary schools. The method used is a qualitative method with a descriptive approach, which allows researchers to obtain an in-depth picture of student attitudes and behaviors related to the value of mutual cooperation. Data collection techniques were carried out through questionnaires, observations, and interviews. The research subjects numbered 28 students, and three of them were selected purposively for in-depth analysis, representing the high, medium, and low categories based on the results of the questionnaire scores. The results showed that the understanding of the value of mutual cooperation was divided into three categories, namely high (39.3%), medium (35.7%), and low (25%). A total of 75% of students showed a fairly good understanding, especially in indicators of involvement in maintaining classroom/school cleanliness, completing assignments responsibly, helping friends selflessly, and working together in groups. However, there were still 25% of students who did not show optimal understanding, especially in aspects of respecting friends' opinions and avoiding blame in group conflict situations. These findings indicate that the value of mutual cooperation has been understood by most students, but still requires reinforcement.